The Little Farthing Rush Light. - Cruikshank, Isaac, 1756?-1811? ? (Fores, S. W., 1792)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons